DIE SLAG VAN BLOEDRIVIER 16 DESEMBER 1838 - De Jong, Robert C. (Scientia Militaria - South African Journal of Military Studies, 2012)
On the site where the brave impi's of Dingane unsuccessfully stormed the wagon-laager of Andries Pretorius and his men 141 years ago, a D-shaped laager of old-fashioned ox-wagons of cast iron blown over with bronze stands today. The laager is a reconstruction of the original, with which the 'Wenkommando' defeated the Zulu might. Bloodriver is one of the battlefields which has been reconstructed to the fullest because of the significance attached to the Battle of Bloodriver in South African military history.